Pelaksanaan Program Jaminan Sosial Ketenagakerjaan Bagi Dosen dan Karyawan Di Yayasan Universitas Islam Sumatera Utara - Saiful Anwar (Universitas Islam Sumatera Utara, 2018)
The Labor Social Security Program so-called the Social Security Organizer Program (BPJS for Health and BPJS for Employment) is organized to provide Social Security, Workforce, Workers in Private Companies, State-Owned Enterprises and other social businesses such as Foundations. Islamic University of North Sumatra (UISU) is a private university organized by Yayasan Universitas Islam Sumatera Utara as a Legal Entity of UISU organizer and as employers for permanent lecturers of Foundations and employees / workers / educational personnel. The purpose of this research is to determine the rules to govern participation, implementation and obstacles and ways to overcome the obstacles in the process of the Social Security Program for foundation lecturers and employees at Islamic University of North Sumatra. This research is analytical descriptive. It is to present a description of the implementation, barriers and ways to overcome the barriers in the Social Security Program. The result shows that in the implementation of the Social Security Program at UISU, different opinions from the respondents are found, and the internal management gets the obstacle that the program is not done by one roof as a union so it causes problems for the labors when moving to another unit. Keywords: Social Security, BPJS for Health, BPJS for Employment, Islamic University of North Sumatra (UISU)